2021
DOI: 10.3389/fendo.2020.609524
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Follicular Fluid Correlates With the Euploid Status of Blastocysts in a Vitamin D Deficient Population

Abstract: ContextThe widespread distribution of the Vitamin D (VitD) receptor in reproductive tissues suggests an important role for VitD in human reproduction. The assessment of patient´s VitD is based on the 25-hydroxyvitamin D (25(OH)D) metabolite measurement. However, most of the circulating 25(OH)D is bound to either VitD-binding protein (VDBP) (88%) or albumin (12%) and less than 1% circulates free.ObjectiveTo determine a possible correlation between VitD levels in serum (S) and follicular fluid (FF) and blastocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…12 Similarly, Anifandis et al demonstrated that FF vitamin D levels were negatively correlated to the quality of embryos and clinical pregnancy rate. 11 On the contrary, in other studies, women with higher FF vitamin D levels were more likely to be pregnant after ART, 14,34,35 have better embryo quality, 34,36 or no significant differences were observed between FF vitamin D levels and pregnancy rate. 13 These discrepancies might have resulted from the fact that the ovarian reserve status was never considered in previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…12 Similarly, Anifandis et al demonstrated that FF vitamin D levels were negatively correlated to the quality of embryos and clinical pregnancy rate. 11 On the contrary, in other studies, women with higher FF vitamin D levels were more likely to be pregnant after ART, 14,34,35 have better embryo quality, 34,36 or no significant differences were observed between FF vitamin D levels and pregnancy rate. 13 These discrepancies might have resulted from the fact that the ovarian reserve status was never considered in previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…However, we did not find any evidence of such a relationship. Although the possible association with oocyte morphology has not previously been assessed, other IVF parameters have been evaluated in the literature; there was no difference in the number of oocytes collected ( 55 , 56 ) or in the oocyte maturation rate as a function of the follicular 25OHD level ( 56 ). Conversely, some researchers have observed a negative correlation between the follicular 25OHD level and the fertilisation rate ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intrafollicular vitamin D levels are positively correlated with oocyte maturity, fertilization rate, and topquality embryos. uid correlated with serum levels of vitamin D. [15] This is thought to be related to the pleiotropic effect of vitamin D, which is related to the vitamin D response element (VDRE) gene, which gives a different phenotype in each cell.…”
Section: Principal Ndingsmentioning
confidence: 99%
“…In a study by Liu et al, a cut-off value of 25(OH)D3 serum of > 14.1 ng/mL can predict a normal fertilization rate, pregnancy rate, and live birth rate. [15] The cut off value of follicular free 25(OH)D3, which can be used as a predictor of top quality embryo (TQE), is > 0.00175 ng/mL (95% CI 0.605 (0.528-0.678), p = 0.0146, sensitivity 34.88%, speci city 85.06%). The relationship between the cut off value of follicle-free 25(OH)D3 levels > 0.00175 ng/mL between the TQE and non-TQE groups differed statistically signi cantly (p = 0.002, OR (95% CI) 3.05(1.46-6) ,38)).…”
Section: Principal Ndingsmentioning
confidence: 99%
See 1 more Smart Citation